Making educational and scholarly videos with screen capture software - Mark L. Burkey (REGION, 2015)
This resource describes several options for making educational videos using "screencasting", or "screen capture" software. The author (who has over 300 screencasted videos on YouTube and indexed on his website, www.burkeyacademy.com) describes the software and hardware tools needed, including some open source and free-to-use tools. Links to some "how to" videos are included, as well as some links to other example videos demonstrating novel professional uses for screencasting.
Keywords: 330; educational resources; screencasting; screen capture